2004
DOI: 10.1148/rg.243035190
|View full text |Cite
|
Sign up to set email alerts
|

MR Lymphangiography: Imaging Strategies to Optimize the Imaging of Lymph Nodes with Ferumoxtran-10

Abstract: Detection of local or regional metastases to lymph nodes is clinically important in virtually any type of primary tumor. Current imaging techniques rely heavily on the size criterion for characterization of nodal disease. However, size can be an ineffective parameter for diagnosis of tumor spread to lymph nodes. Magnetic resonance (MR) imaging performed before and after administration of ferumoxtran-10 is a promising technique for characterization of lymph nodes in patients with various primary tumors. Normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 28 publications
0
55
0
2
Order By: Relevance
“…We think that this problem may have been amplified in our study since a high-resolution technique using phased-array coils and/or three-dimensional techniques was not available at that time in our institution. This is especially true for the GRE T2-weighted sequences, which are more prone to suffer from magnetic susceptibility artifacts and possess lower spatial resolution (35).…”
Section: Discussionmentioning
confidence: 99%
“…We think that this problem may have been amplified in our study since a high-resolution technique using phased-array coils and/or three-dimensional techniques was not available at that time in our institution. This is especially true for the GRE T2-weighted sequences, which are more prone to suffer from magnetic susceptibility artifacts and possess lower spatial resolution (35).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that an insufficient dose of USPIO contrasting agent may result in false-positive findings during USPIO-enhanced MRI (20). Thus, based on several dosage studies for USPIO (21)(22)(23), 90 mmol Fe/kg (equal to 5 mg/kg Fe particles) was used in this study in order to avoid the influence by inadequate dosing.…”
Section: Discussionmentioning
confidence: 99%
“…T2-weighted imaging can be a good subjective indicator reflecting enhancement levels, but it does not reflect actual T2 relaxation time changes due to varying prescan parameters and system stability (34). The T2* value was tested but its signal diminished quickly to background levels at longer TEs, which prohibits accurate calculation of T2* or R2' values (35). Therefore, T2 values were used to calculate enhancement ratios in order to reflect the extent of changes and accounted for individual differences in the current study.…”
Section: Possible Value Of T2 Enhancement Ratiomentioning
confidence: 99%
“…Normal lymph nodes become dark in signal intensity after ferumoxtran-10 administration due to shortening of T2 and T2* relaxation times of water protons, whereas metastatic deposits within lymph nodes remain bright. 34,35 This agent has been used to evaluate lymph nodes in the setting of a wide variety of malignancies. For example, Deserno et al showed that ferumoxtran-10-enhanced MRI significantly improved nodal staging in those with bladder carcinoma by depicting metastases even in normal-sized lymph nodes, with accuracy, sensitivity, specificity, and positive and negative predictive values of 95%, 96%, 95%, 89%, and 98%, respectively.…”
Section: Functional Lymph Node Imagingmentioning
confidence: 99%